Corneal nerves in health and disease. (November 2019) - Al-Aqaba, Mouhamed A.; Dhillon, Virinder K.; Mohammed, Imran; Said, Dalia G.; Dua, Harminder S.
Abstract: The cornea is the most sensitive structure in the human body. Corneal nerves adapt to maintain transparency and contribute to corneal health by mediating tear secretion and protective reflexes and provide trophic support to epithelial and stromal cells. The nerves destined for the cornea travel from the trigeminal ganglion in a complex and coordinated manner to terminate between and within corneal epithelial cells with which they are intricately integrated in a relationship of mutual support involving neurotrophins and neuromediators. The nerve terminals/receptors carry sensory impulses generated by mechanical, pain, cold and chemical stimuli. Modern imaging modalities have revealed a range of structural abnormalities such as attrition of nerves in neurotrophic keratopathy and post-penetrating keratoplasty; hyper-regeneration in keratoconus; decrease of sub-basal plexus with increased stromal nerves in bullous keratopathy and changes such as thickening, tortuosity, coiling and looping in a host of conditions including post corneal surgery. Functionally, symptoms of hyperaesthesia, pain, hypoaesthesia and anaesthesia dominate. Morphology and function do not always correlate. Symptoms can dominate in the absence of any visible nerve pathology and vice-versa. Sensory and trophic functions too can be dissociated with pre-ganglionic lesions causing sensory loss despite preservation of the sub-basal nerve plexus and minimal neurotrophic keratopathy. Structural and/or functional nerve anomalies can be induced by corneal pathology and conversely, nerve pathology can drive inflammation and corneal pathology. Improvements in accuracy of assessing sensory function and imaging nerves in vivo will reveal more information on the cause and effect relationship between corneal nerves and corneal diseases. Highlights: Sub-basal bulb-like structures and Limbal nerve corpuscles have not yet been attributed a definitive function. Dissociation of trophic and sensory functions and a discordance between objective signs and subjective symptoms is common. 'Pain without stain' and 'stain without pain' reflect stages of nerve pathology from hyperaesthesia to anaesthesia. Structural and/or functional nerve changes occur in all forms of corneal pathology. A wide range of changes in nerve morphology are seen a large variety of corneal diseases and following surgery. Inflammatory responses of resident epithelial cells, keratocytes and dendritic cells are integral to corneal nerve responses.